2003
DOI: 10.1111/j.1439-0272.2003.tb00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial and ureaplasmal infections in patients with nonbacterial chronic prostatitis

Abstract: Our study was designed to establish the necessity of routine evaluation of patients with inflammatory (IIIA) and noninflammatory (IIIB) types of nonbacterial prostatitis (NBP) for chlamydial and ureaplasmal infections. From 1999 to 2001, 165 patients with a mean age of 35 years (range 20-54 years) were evaluated for the syndrome of chronic prostatitis. The evaluation included scoring with Prostate Symptom Score Index (PSSI) and NIH Chronic Prostatitis Symptom Index (CPSI), Meares-Stamey test and culturing of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Although it was not clear whether the dorso-lateral prostate was involved or not this model demonstrated two distinct histological phases of bacterial inflammation in the ventral prostate. 73 During the initial acute infection stage (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14] an acute response to the bacterial challenge with florid infiltration of polymorphonuclear cells into bacteria-containing spaces was observed. 74 As the infections became chronic, heavy lymphocyte infiltration and fibrous tissue proliferation completely engulfed the ventral prostatic lobe.…”
Section: Rat Models Of Prostatitis (Categories I and Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was not clear whether the dorso-lateral prostate was involved or not this model demonstrated two distinct histological phases of bacterial inflammation in the ventral prostate. 73 During the initial acute infection stage (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14] an acute response to the bacterial challenge with florid infiltration of polymorphonuclear cells into bacteria-containing spaces was observed. 74 As the infections became chronic, heavy lymphocyte infiltration and fibrous tissue proliferation completely engulfed the ventral prostatic lobe.…”
Section: Rat Models Of Prostatitis (Categories I and Ii)mentioning
confidence: 99%
“…10,12,13 The remaining 60-95% cases of clinical prostatitis (categories IIIA and IIIB) may involve (i) hormonal imbalance; 14,15 (ii) neurological dysfunction; 16,17 (iii) a-adrenergic system abnormalities; [18][19][20] (iv) urinary reflux into the prostate; [21][22][23] (v) inappropriate cytokine release [24][25][26][27][28][29][30][31][32] and/or (vi) an autoimmune response. [33][34][35][36][37] The patients typically have repeat episodes of prostatitis and therapy is 'hit or miss'.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic bacterial prostatitis, the spectrum of strains is wider. The significance of intracellular bacteria, such as C. trachomatis, is uncertain [257]. In patients with immune deficiency or HIV infection, prostatitis may be caused by fastidious pathogens, such as M. tuberculosis, Candida sp.…”
Section: I33mentioning
confidence: 99%
“…Ureaplasma urealyticum is a self-replicating prokaryote belonging to the taxonomic class Mollicutes, which lack a cell wall. Genital U. urealyticum colonization has been found to be involved in non-gonococcal urethritis (NGU), prostatitis, epididymitis and infertility [6,7]. Some investigators reported that the presence of U. urealyticum in semen was related to a decrease in sperm density, motility and morphology [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%